Obesity as a Risk Factor of Erosive Gastroesophageal Reflux Disease - Hotmen Sijabat; Marcellus Simadibrata; Ari Fahrial Syam; Endang Susalit; Djulzasri Albar; Abdul Aziz Rani (The Indonesian Society for Digestive Endoscopy, 2010)
Background: Gastroesophageal reflux disease (GERD) is a pathological condition of esophagus caused by reflux of gastric content or gastric juice with multifactorial etiologies. Some complications may occur such as: ulcer, bleeding, stricture, Barret’s esophagus and esophageal adenocarcinoma. One of risk factors that currently taken into concern is obesity. Our study aimed to identify obesity and abdominal obesity as the risk factor in the development of erosive GERD and to recognize that abdominal obesity is more important factor compared to obesity itself as the risk factor on the incidence of erosive GERD.. Method: Our study was a cross-sectional study. Data was obtained from eligible patients at Division of Gastroenterology, Department of Internal Medicine, Faculty of Medicine, University of Indonesia between June and September 2009 Results: Samples were 74 patients with mean age of 48.61 ± 8.64 years. The proportion of female patients was larger than male (60.81% vs. 39.19%). The endoscopic assessment of upper gastrointestinal tract based on Los Angeles Classification included: Grade A esophagitis: 27.03%, Grade B: 16.21%, Grade C: 4.05%, Grade D: 1.35%. Obesity (odds ratio (OR) 17.160; 95% confidence interval (CI) 5.219 – 56.418, p = 0.000) and abdominal obesity (OR 10.371, 95% CI 3.260 – 32.915; p = 0.000) has been proven as risk factors in the development of erosive GERD. Conclusion: There is a correlation between obesity and abdominal obesity as risk factors on the development of erosive GERD. Obesity becomes a more important factor compared to abdominal obesity as the risk factor on the development of erosive GERD. Keywords: erosive gastroesophageal reflux disease, obesity, abdominal obesity, risk factor